Жизнь Рамакришны: пер. с фр. / Р. Роллан ; пер.: А. А. Полляк, Э. Б. Шлосберг - Роллан Ромен (Политиздат, 1991)
Экземпляры: Абонемент (20161024) / Инвентарный номер: 29533 / Цена: 3.80 / Авт.знак: Р 67 / ГРНТИ: 17 / ББК: 84(4Фра)